Red Palm: exploring service quality and servicescape of the best backpacker hostel in Asia - Musa, G.; Thirumoorthy, T. (Taylor & Francis (Routledge), 2011)
The Red Palm was voted the best backpacker’s hostel in Asia for 2006. This study explores the reasons behind this phenomenal achievement by examining service quality and servicescape of the establishment. Using NVIVO software, data from 192 website comments and eighteen in-depth interviews were content-analysed. The results show that the most important dimension of service quality experience with the Red Palm is tangibles, followed by empathy and assurance. The most important tangible elements of the Red Palm are facilities and equipment, location and the atmosphere of friendliness, welcome and homeliness, and cleanliness. The excellent staff elements include their courtesy, individualised attention and willingness to help. The paper also presents the illustration of Bitner’s [(1992). Servicescapes: The impact of physical surroundings on customers and employees. The Journal of Marketing, 56(2), 57–71] servicescape framework in relation to the Red Palm.